Attention and word learning in autistic, language delayed and typically developing children - Tenenbaum, Elena; Amso, Dima; Abar, Beau W.; Sheinkopf, Stephen J. (Frontiers in Psychology, 2014)
Previous work has demonstrated that patterns of social attention hold predictive value for language development in typically developing infants. The goal of this research was to explore how patterns of attention in autistic, language delayed, and typically developing children relate to early word learning and language abilities. We tracked patterns of eye movements to faces and objects while children watched videos of a woman teaching them a series of new words. Subsequent test trials measured participants’ recognition of these novel word-object pairings. Results indicated that greater attention to the speaker’s mouth was related to higher scores on standardized measures of language development for autistic and typically developing children (but not for language delayed children). This effect was mediated by age for typically developing, but not autistic children. When effects of age were controlled for, attention to the mouth among language delayed participants was negatively correlated with standardized measures of language learning. Attention to the speaker’s mouth and eyes while she was teaching the new words was also predictive of faster recognition of the newly learned words among autistic children. These results suggest that language delays among children with autism may be driven in part by aberrant social attention, and that the mechanisms underlying these delays may differ from those in language delayed participants without autism.